Effect Of An Animated Prenatal Education Video On Intrauterine Father Attachment: A Pilot Pretest-Posttest Study - Ika Parmawati; Firly Sofia Hanum; Ukke Yuristian; Salsabilla Aryuna Tantra; Elsi Dwi Hapsari; Ayyu Sandhi (Caring: Indonesian Journal of Nursing Science, 2026)
Father-fetus attachment affects maternal and fetal health, yet few interventions enhance it. Although relaxation, music, and fetal visualitation based education is recommended, evidence remains limited. Structured three-segment animated prenatal education (maternal changes, fetal development, and attachment strategies) remains rarely implemented for expectant fathers. This study aimed to determine the effect of an animated video-based prenatal health education intervention on intrauterine father–fetus attachment among expectant fathers. A pre-experimental one-group pretest-posttest study was conducted among 41 expectant fathers recruited through consecutive sampling from two primary health centers. Attachment was measured using the Intrauterine Father Attachment Scale (Cronbach’s α = 0.939). Normality was assessed using the Shapiro–Wilk test. Pre-post differences were analyzed using the Wilcoxon Signed Rank Test, and associations with participant characteristics were examined using correlation and group comparison tests as appropriate (p<0.05). Although the median intrauterine father attachment score increased from pretest to posttest [69.00 (IQR 61.50–74.00) vs 70.00 (IQR 64.00–78.50)], the difference was not statistically significant (p = 0.069). The animated video intervention did not significantly improve intrauterine father–fetus attachment. Further studies using more interactive or multi-component interventions are warranted. Keyword: Intrauterine Father Attachment, Paternal Behavior, Health Education,  Video-Audio Media, Pregnancy